2022
DOI: 10.1161/jaha.121.024916
|View full text |Cite
|
Sign up to set email alerts
|

DR‐FLASH Score Is Useful for Identifying Patients With Persistent Atrial Fibrillation Who Require Extensive Catheter Ablation Procedures

Abstract: Background Modification of arrhythmogenic substrates with extensive ablation comprising linear and/or complex fractional atrial electrogram ablation in addition to pulmonary vein isolation (PVI‐plus) can theoretically reduce the recurrence of atrial fibrillation. The DR‐FLASH score (score based on diabetes mellitus, renal dysfunction, persistent form of atrial fibrillation, left atrialdiameter >45 mm, age >65 years, female sex, and hypertension) is reportedly useful for identifying patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…15 In a previous subanalysis of the EARNEST-PVI trial, we reported that a DR-FLASH score >3, based on identifiable preprocedural patient characteristics, indicated the effectiveness of the PVI-plus strategy. 7 The present study stratified patients based on electrophysiological findings during ablation procedures, suggesting that combining both approaches could enhance stratification efficacy. Although the analysis was exploratory in nature, we divided patients into groups according to DR-FLASH score (>3 or ≤3) and whether they were part of Group D. The results indicated that patients with DR-FLASH scores >3, particularly those in Group D, may especially benefit from the PVI-plus strategy.…”
Section: Patient Selection For Additional Ablationmentioning
confidence: 88%
See 1 more Smart Citation
“…15 In a previous subanalysis of the EARNEST-PVI trial, we reported that a DR-FLASH score >3, based on identifiable preprocedural patient characteristics, indicated the effectiveness of the PVI-plus strategy. 7 The present study stratified patients based on electrophysiological findings during ablation procedures, suggesting that combining both approaches could enhance stratification efficacy. Although the analysis was exploratory in nature, we divided patients into groups according to DR-FLASH score (>3 or ≤3) and whether they were part of Group D. The results indicated that patients with DR-FLASH scores >3, particularly those in Group D, may especially benefit from the PVI-plus strategy.…”
Section: Patient Selection For Additional Ablationmentioning
confidence: 88%
“…6 Using the 1-year followup results, we reported that a DR-FLASH score (based on diabetes, renal dysfunction, PerAF, left atrial [LA] diameter >45 mm, age >65 years, female sex, and hypertension) >3, which is a predictor of a low voltage area, could distinguish patients who would and would not benefit from additional substrate ablation. 7 Considering the results of previous studies that could not prove the efficacy of additional substrate ablation, 1,8 there is likely to be a certain proportion of the population who will not benefit from additional substrate ablation. Theoretically, additional ablation has an increased risk of complications and it is worth detecting specific patients who would benefit from the PVI-plus strategy.…”
Section: Catheter Ablation Proceduresmentioning
confidence: 99%
“…A subanalysis of the EARNEST‐PVI trial reported that the efficacy of left atrial ablation in addition to PVI was enhanced in patients with a high DR‐FLASH score, a risk score that predicts the presence of left atrial low‐voltage areas. 25 , 26 A prior study suggested that complete conduction block could be easily achieved in areas with reduced bipolar voltage. 27 In addition, left atrial linear ablation guided by low‐voltage areas demonstrated better rhythm outcomes than linear ablation without voltage guidance.…”
Section: Discussionmentioning
confidence: 99%
“…According to reports, it can be used to detect patients who have arrhythmogenic substrates. Based on the DR-FLASH score, patients with persistent atrial fibrillation can be categorized into two groups, according to Sato et al (23) hypothesis: those who require PVI-plus and those who can get by with PVI alone.…”
Section: Discussionmentioning
confidence: 99%